Anticoagulant effects of statins and their clinical implications - Undas, Anetta; Brummel-Ziedins, Kathleen E.; Mann, Kenneth G. (Thrombosis and Haemostasis, 2014)
There is evidence indicating that statins (3-hydroxy-methylglutaryl coenzyme A reductase inhibitors) may produce several cholesterol-independent antithrombotic effects. In this review, we provide an update on the current understanding of the interactions between statins and blood coagulation and their potential relevance to the prevention of venous thromboembolism (VTE). Anticoagulant properties of statins reported in experimental and clinical studies involve decreased tissue factor expression resulting in reduced thrombin generation and attenuation of pro-coagulant reactions catalysed by thrombin, such as fibrinogen cleavage, factor V and factor XIII activation, as well as enhanced endothelial thrombomodulin expression, resulting in increased protein C activation and factor Va inactivation. Observational studies and one randomized trial have shown reduced VTE risk in subjects receiving statins, although their findings still generate much controversy and suggest that the most potent statin rosuvastatin exerts the largest effect.
Keywords: Blood coagulation; statins; tissue factor; thrombin; venous thromboembolism